Case Study on the Genetic Parameters and Possibilities of Selecting Gilts for Traits Monitored in the Performance Test - Nenad Stojiljković; Čedomir Radović; Marija Gogić; Vladimir Živković; Aleksandra Petrović; Krstina Zeljić Stojiljković; Dubravko Škorput (Veterinary Sciences)
This research examined the phenotypic and genotypic variability of traits assessed in the gilt performance test and their subsequent impact on gilt selection. The traits evaluated in the gilt performance test were analyzed on two pig farms over a period of 3 consecutive years. A total of 3664 gilts were included in the research. At the end of the test, body weight, backfat thickness (BF1 and BF2), and longissimus dorsi muscle depth (MLD) were measured using an ultrasound device. The following breeds were evaluated on the farms: Landrace (L)–1981 gilts, Large White (LW)–1344 gilts, and Duroc (D)–339 gilts. In the analyzed population, direct genetic effects accounted for 0.2647 of the total variation in age at the end of the test (AET). Heritability coefficients of 0.37 for BF1 and 0.35 for BF2 indicate that these traits are highly heritable in the studied population. On the other hand, the heritability coefficient for the depth of MLD, which is 0.23, places this trait in the group of medium heritable traits. High heritability coefficients of these traits indicate great potential for genetic improvement through selection. The use of well-designed selection programs aimed at these traits can significantly accelerate the genetic improvement of the population and have an impact on the economic profit of pork production.